Squashing the Beef: Why American Animal Rights Advocates Should Start Liking Jewish and Islamic Law - Saeed, Samier (Columbia Journal of Environmental Law, 2022)
Animal rights advocates in the West decry the mistreatment of animals, such as their use in experimentation and, most notoriously, factory farming. They identify the fact that animals are legally considered mere property as the source of these abuses. They also tend to view Abrahamic religions as responsible for this paradigm and in conflict with animal rights. The most flashpoint in this context is the battle over Jewish and Muslim ritual slaughter. However, this Note argues, animal rights advocates mistarget their animosity. Jewish and Islamic law are quite favorable towards animals in comparison to American law, and while they obviously do not go as far as animal rights advocates would like in according rights to animals, they do cohere with modern animal rights views in several ways, such as by according animals a legal status distinct from mere property, subjecting the use of animals for food to heightened scrutiny, and providing more clearly for the enforcement of animal protection laws. As animal rights advocates and their opponents continue to debate the extent to which animals should be accorded greater legal protections under American law, these religious traditions show that the matters they are debating were considered and debated by Muslim and Jewish jurists thousands of years ago, and that, far from impeding animal rights, religious bodies of law constitute a positive example that can help advance them.